PENGARUH PENERAPAN TEKNIK MNEMONIC TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS V SD INPRES 6/75 TA KABUPATEN BONE - Rukayah, Rukayah; Jafar, Muh. Idris; Yulianti, Lilis (Bestari: Jurnal Pendidikan dan Kebudayaan, 2025)
Abstract: Abstract: This research is a quantitative study with a One Group Pretest Posttest design aimed at determining the effect of applying Mnemonic techniques on the poetry writing ability of fifth-grade students at SD Inpres 6/75 TA, Bone Regency. This study involved 22 fifth-grade students as samples using the saturated sampling technique. The data collection technique was carried out through pretest and posttest poetry writing ability tests. Based on the results of descriptive statistical analysis, the average pretest score of the students was 42.0455, which falls into the "Poor" category, whereas the average posttest score increased to 73.0114, which falls into the "Good" category. These results indicate an improvement in students' poetry writing skills after the application of the Mnemonic technique. Furthermore, based on the results of the inferential statistical analysis using the Paired Sample t-Test, a t-value of (15.541) was obtained, which is greater than the t-table value (2.07961) and is significant at 0.000 0.05. Thus, H0 is rejected and H1 is acceptedKey Words: Mnemonic technique, ability, poetry writing.